2021
DOI: 10.3390/rs13112187
|View full text |Cite
|
Sign up to set email alerts
|

Building Extraction from Very-High-Resolution Remote Sensing Images Using Semi-Supervised Semantic Edge Detection

Abstract: The automated detection of buildings in remote sensing images enables understanding the distribution information of buildings, which is indispensable for many geographic and social applications, such as urban planning, change monitoring and population estimation. The performance of deep learning in images often depends on a large number of manually labeled samples, the production of which is time-consuming and expensive. Thus, this study focuses on reducing the number of labeled samples used and proposing a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…[11] first pre-trained a Fully Convolutional Network [47] (FCN) with raw OSM and then fine-tuned the model with a relatively small amount of clean labels. Although [11] significantly reduced labeling cost by applying a common practice of transfer learning, it requires some portion of clean verified labels, similar to the assumption of the semi-supervised learning set-up [12][13][14]. [23] also confirmed that pre-training with noisy OSM labels benefits deep learning performance and further found that a large amount of OSM labels can be beneficial compared to a small number of clean labels.…”
Section: B Noisy Supervisionmentioning
confidence: 68%
See 2 more Smart Citations
“…[11] first pre-trained a Fully Convolutional Network [47] (FCN) with raw OSM and then fine-tuned the model with a relatively small amount of clean labels. Although [11] significantly reduced labeling cost by applying a common practice of transfer learning, it requires some portion of clean verified labels, similar to the assumption of the semi-supervised learning set-up [12][13][14]. [23] also confirmed that pre-training with noisy OSM labels benefits deep learning performance and further found that a large amount of OSM labels can be beneficial compared to a small number of clean labels.…”
Section: B Noisy Supervisionmentioning
confidence: 68%
“…However, we still witnessed a performance gap of SFL compared to the strong supervision case. Although not investigated in this study, integrating SFL with labelrefinement [41][42][43], pre-trained models [11,23], or semisupervised methods [12][13][14] may further close the gap to the strong supervision in practical use.…”
Section: G Discussion Of Results and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important to update the information of features in a timely manner and grasp the development and changes of urban space to guide the planning of cities. Among them, the traditional method mainly relies on the relevant staff's industry experience and professional knowledge to collect the feature information, which is time-consuming and labor-intensive 1 . With the rapid development of remote sensing technology, it has achieved wide application in urban planning 2 , crop extraction 3 , and resource monitoring 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of environmental indicator monitoring, machine learning algorithms such as Support Vector Machine (SVM) have been used to assess the percentage of agricultural land contaminated by plastic [7]. For detection of buildings, a semi-supervised deep learning method based on edge detection network D-LinkNet has been designed to understand the distribution of the buildings [8], which is useful for urban planning, change monitoring and population estimation.…”
Section: Introductionmentioning
confidence: 99%